Who was Seabiscuit? - Buckley, James Jr 1963-; Copeland, Gregory (New York, New York Grosset & Dunlap, an imprint of Penguin Random House, 2015)
Describes the life and accomplishments of the race horse Seabiscuit, who thrived with a loving jockey and trainer and won the hearts of millions around the country
Who Was Seabiscuit? -- A Runty Little Thing -- A New Beginning -- The Perfect Team -- Rise of the Biscuit -- Big Wins and a Big Loss -- The Fans Want a Race! -- The Match Race -- a Big Step Backward -- A Triumphant Return -- Seabiscuit's Legacy -- Timelines -- Bibliography
The World around us
Includes bibliographical references (pages 104-105)
1
Keywords: Seabiscuit -- (Race horse) -- 1933-1947 -- Juvenile literature; Horse racing -- United States -- Juvenile literature; Horse racing; Race horses -- United States -- Biography -- Juvenile literature; Race horses; Seabiscuit (Race horse); Horse racing; Race horses; Seabiscuit (Race horse); United States; Biography; Juvenile works